International economics : Theory and policy - Krugman, Paul R.; Obstfeld, Maurice (New York Addison Wesley, 2000)
This book covers regional economic issues (including location theory), optimum currency areas and the European Community, and the problems of former communist countries in the transition to a market economy. Topical new applications include the US oilseed dispute with Europe, the BCCI scandal, Third-World debt forgiveness and "1980-1993 - disinflation, recovery and the global slump".
Includes bibliographical references and index
Keywords: Quản trị kinh doanh